2017
DOI: 10.1111/eva.12507
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating evolutionary insights to improve ecotoxicology for freshwater species

Abstract: Ecotoxicological studies have provided extensive insights into the lethal and sublethal effects of environmental contaminants. These insights are critical for environmental regulatory frameworks, which rely on knowledge of toxicity for developing policies to manage contaminants. While varied approaches have been applied to ecotoxicological questions, perspectives related to the evolutionary history of focal species or populations have received little consideration. Here, we evaluate chloride toxicity from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 77 publications
1
38
0
Order By: Relevance
“…This is because the strong selection imposed by these stressors can lead to rapid evolutionary changes (Hendry, 2016). Rapid evolution increasing the tolerance to warming (e.g., Geerts et al., 2015; Ljungfeldt, Quintela, Besnier, Nilsen, & Glover, 2017) and to contaminants (e.g., Brady et al., 2017; Turko, Sigg, Hollender, & Spaak, 2016) has indeed been reported. Yet, despite the increasing concern for interactions between warming and contaminants, we do not know how rapid evolution in response to warming changes the toxicity of contaminants at higher temperatures.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…This is because the strong selection imposed by these stressors can lead to rapid evolutionary changes (Hendry, 2016). Rapid evolution increasing the tolerance to warming (e.g., Geerts et al., 2015; Ljungfeldt, Quintela, Besnier, Nilsen, & Glover, 2017) and to contaminants (e.g., Brady et al., 2017; Turko, Sigg, Hollender, & Spaak, 2016) has indeed been reported. Yet, despite the increasing concern for interactions between warming and contaminants, we do not know how rapid evolution in response to warming changes the toxicity of contaminants at higher temperatures.…”
Section: Introductionmentioning
confidence: 85%
“…This is because the strong selection imposed by these stressors can lead to rapid evolutionary changes (Hendry, 2016). Rapid evolution increasing the tolerance to warming (e.g., Geerts et al, 2015;Ljungfeldt, Quintela, Besnier, Nilsen, & Glover, 2017) and to contaminants (e.g., Brady et al, 2017;Turko, Sigg, Hollender, & Spaak, 2016) has indeed been reported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…to high road salt concentrations over multiple generations may underestimate the sensitivity of naïve individuals in uncontaminated systems (also seeBrady, Richardson, & Kunz, 2017).…”
mentioning
confidence: 99%